Structural Health Monitoring for Bridge Crane Based on Low Temperature-Sensitivity FBG Sensors - Zhaobo, Zhang; Sheng, Liu; Yibo, Wei; Hongnan, Li (Frontiers in Physics, 2021)
Accurate measurement of the stain variation and effective distinguishment of the temperature-induced stress from the load-induced stress have been major objectives for strain sensors in crane monitoring. In this paper, a fiber Bragg grating (FBG) strain sensor with low temperature-sensitivity, packaged by two gripper tubes and stainless-steel tubes, is presented and applied in a bridge crane health monitoring project. Calibration experiments and reliability tests are conducted to evaluate the stain transferring characteristics of the sensors in a laboratory environment. On the other hand, the on-site tests show that these FBG strain sensors have the advantage of precision, reliability, and applicability. Meanwhile, the low temperature-sensitivity nature of the sensors is verified by the test results, which shows its promising potential in the health monitoring for a bridge crane.